Phase IA/IB study of single-agent tislelizumab, an investigational anti-PD-1 antibody, in solid tumors - Yun Zhang; Bhumsuk Keam; Jayesh Desai; Ben Markman; Shahneen Sandhu; Michael Millward; Yoon-Koo Kang; Chia-Chi Lin; Yee Chao; Sanjeev Deva; Jong Seok Lee; Chia-Jui Yen; et al. (Journal for ImmunoTherapy of Cancer)
Background The programmed cell death-1/programmed cell death ligand-1 (PD-1/PD-L1) axis plays a central role in suppressing antitumor immunity; axis dysregulation can be used by cancer cells to evade the immune system. Tislelizumab, an investigational monoclonal antibody with high affinity and binding specificity for PD-1, was engineered to minimize binding to FcγR on macrophages to limit antibody-dependent phagocytosis, a potential mechanism of resistance to anti-PD-1 therapy. The aim of this phase IA/IB study was to investigate the safety/tolerability, antitumor effects and optimal dose and schedule of tislelizumab in patients with advanced solid tumors.Methods Patients (aged ≥18 years) enrolled in phase IA received intravenous tislelizumab 0.5, 2, 5 or 10 mg/kg every 2 weeks; 2 or 5 mg/kg administered every 2 weeks or every 3 weeks; or 200 mg every 3 weeks; patients in phase IB received 5 mg/kg every 3 weeks. Primary objectives were to assess tislelizumab’s safety/tolerability profile by adverse event (AE) monitoring and antitumor activity using RECIST V.1.1. PD-L1 expression was assessed retrospectively with the VENTANA PD-L1 (SP263) Assay.Results Between May 2015 and October 2017, 451 patients (n=116, IA; n=335, IB) were enrolled. Fatigue (28%), nausea (25%) and decreased appetite (20%) were the most commonly reported AEs. Most AEs were grade 1–2 severity; anemia (4.9%) was the most common grade 3–4 AE. Treatment-related AEs led to discontinuation in 5.3% of patients. Grade 5 AEs were reported in 14 patients; 2 were considered related to tislelizumab. Pneumonitis (2%) and colitis (1%) were the most common serious tislelizumab-related AEs. As of May 2019, 18% of patients achieved a confirmed objective response in phase IA and 12% in phase IB; median follow-up duration was 13.6 and 7.6 months, respectively. Pharmacokinetics, safety and antitumor activity obtained from both phase IA and IB determined the tislelizumab recommended dose; ultimately, tislelizumab 200 mg intravenous every 3 weeks was the dose and schedule recommended to be taken into subsequent clinical trials.Conclusions Tislelizumab monotherapy demonstrated an acceptable safety/tolerability profile. Durable responses were observed in heavily pretreated patients with advanced solid tumors, supporting the evaluation of tislelizumab 200 mg every 3 weeks, as monotherapy and in combination therapy, for the treatment of solid tumors and hematological malignancies.Trial registration number NCT02407990.